INFORMASI ANATOMI DAUN DIKOTIL PADA INTENSITAS CAHAYA YANG BERBEDA SEBAGAI MEDIA ATLAS - Fransiska, Nadia; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Media atlas equipped with anatomical information on the leaves of ornamental dicot plants at different light intensities can be used as a learning medium to make it easier for students to distinguish plant tissues, especially leaf tissues in the structure and function submaterial of class XI plant tissues. The purpose of this study was to make a media atlas and to determine its feasibility. The research method used was descriptive quantitative. The stages of making atlas media were pre-production, production and post-production. The atlas media was validated using an instrument of questionnaire and a media questionnaire using a Likert scale. The media questionnaire contained four aspects of assessment, namely aspects of presentation, content, language, and usage with 21 indicators. The atlas media validator was carried out by 2 Biology Education lecturers and 3 Biology teachers for class XI SMA. The results of the validation obtained a CVI value of 0.98 so that it was not yet valid. Therefore, the atlas media needs to be improved, especially on the content aspect before being used in the learning process.